STANDARDS COMMITTEE Journey to Guidelines - Part Two: “The Road is Long….” - ORNAC, ORNAC (Operating Room Nurses Association of Canada Journal, 2016)
Welcome back to the second article on the transition of the ORNAC Standards to Guidelines. In this article we will introduce our validation team, discuss how we selected on sections 3 and 4 for review, and explain levels of evidence and our approach to adding levels of evidence to our document.